Moderasi Beragama Solusi dalam Kepura-puraan: : Analisa Sosiologis Antiklimaks Pluralisme - Walean, Jefrie (STT Bala Keselamatan Palu, 2024)
Abstract: Religious diversity in Indonesia is both a potential and a challenge. In the context of pluralism, religious moderation is a solution to prevent conflict and build harmony between religious communities. However, religious moderation can also be a pretense, where individuals or groups only show tolerance on the surface, but do not actually have a deep commitment to the values ​​of moderation. This research aims to analyze the phenomenon of religious moderation in the context of pluralism in Indonesia, with a focus on the anticlimax of pluralism. Through sociological analysis, this research identifies factors that encourage and hinder religious moderation, as well as their impact on relations between religious communities. The research results show that religious moderation in Indonesia still faces various challenges. One of the main challenges is anticlimactic pluralism, where individuals or groups show an attitude of tolerance on the surface, but actually do not have a deep commitment to the values ​​of moderation. This can cause misunderstandings and conflicts between religious believers. This research also finds that sincere and deep religious moderation can be achieved through inclusive and critical religious education, as well as through open and constructive inter-religious dialogue. Abstrak: Keberagaman agama di Indonesia menjadi potensi sekaligus tantangan. Dalam konteks pluralisme, moderasi beragama menjadi solusi untuk mencegah konflik dan membangun harmoni antarumat beragama. Namun, moderasi beragama juga bisa menjadi kepura-puraan, di mana individu atau kelompok hanya menunjukkan sikap toleransi di permukaan, tetapi sebenarnya tidak memiliki komitmen yang mendalam terhadap nilai-nilai moderasi. Penelitian ini bertujuan untuk menganalisis fenomena moderasi beragama dalam konteks pluralisme di Indonesia, dengan fokus pada antiklimaks pluralisme. Melalui analisis sosiologis, penelitian ini mengidentifikasi faktor-faktor yang mendorong dan menghambat moderasi beragama, serta dampaknya terhadap hubungan antarumat beragama. Hasil penelitian menunjukkan bahwa moderasi beragama di Indonesia masih menghadapi berbagai tantangan. Salah satu tantangan utama adalah antiklimaks pluralisme, di mana individu atau kelompok menunjukkan sikap toleransi di permukaan, tetapi sebenarnya tidak memiliki komitmen yang mendalam terhadap nilai-nilai moderasi. Hal ini dapat menyebabkan kesalahpahaman dan konflik antarumat beragama. Penelitian ini juga menemukan bahwa moderasi beragama yang tulus dan mendalam dapat dicapai melalui pendidikan agama yang inklusif dan kritis, serta melalui dialog antarumat beragama yang terbuka dan konstruktif.